The effects of combined training on interluken-6 and C reactive protein as non-traditional cardio risk factors in inactive students - Esmaelzadeh Toloee, Mohammad Reza; Soh, Kim Geok; Abdullah, Muhammad Nazrul Hakim; Abu Samah, Bahaman (Universiti Putra Malaysia Press, 2012)
Studies have shown a positive association between regular physical activity and reduction of cardio risk factors. The objective of this research was to examine the effects of combined training on some cardio risk factors in inactive students. Thirty healthy inactive men were assigned into two groups: 1) combined training (CTG) (n=15), 2) no-training (NTG) (n=15). The CTG performed 5 resistance exercises and this was followed by 30 minutes of endurance training with 60% -80% HRmax for 8 weeks (3 days per week). Meanwhile, the NT group continued the same activity routine that they had used prior to becoming a study participant. Pre- and post-measures included VO2max, muscle strength, body composition, and blood cardio risk factors. The VO2max and muscle strength significantly (P<0.05) increased in CTG. The percentage of body fat tended to slightly decrease (P>0.05) and skeletal muscle mass significantly increased in CTG (+0.85kg, P = 0.003). However, these parameters did not show any change in NTG. The concentrations of total cholesterol, TG and LDL in the blood did not significantly change during the study in the two groups (P> 0.05). HDL significantly improved after week 8 of combined training in the CTG. Furthermore, CRP did not change in the two groups (P> 0.05), while the level of interleukin-6 had decreased significantly in the CTG. The results of this study have shown that combined training improves some cardio risk factors, cardiorespiratory fitness, as well as muscle strength and body composition in inactive students.